ANALISIS PENERAPAN AKAD IMBT PADA PRODUK PEMBIAYAAN DI BANK ACEH SYARIAH DALAM PERSPEKTIF FATWA DSN MUI NO.27/DSN-MUI/III/2002 - Cut Zainab Safira; Khadijatul Musanna (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the application of the Ijarah Muntahiya Bittamlik (IMBT) contract in financing products at Bank Aceh Syariah from the perspective of DSN-MUI Fatwa No. 27/DSN-MUI/III/2002. The IMBT contract represents a hybrid financing scheme combining leasing (ijarah) with ownership transfer at the end of the contract period, making it a strategic instrument in fulfilling customers’ needs for productive assets within Islamic banking. This research aims to analyze the normative framework of the IMBT contract based on the DSN-MUI fatwa and to evaluate its practical implementation at Bank Aceh Syariah in terms of sharia compliance. The study employs a qualitative method with a normative-juridical and empirical approach. Data are collected through literature review of relevant legal sources and analysis of actual financing practices within the institution. The findings reveal that, substantively, the implementation of the IMBT contract at Bank Aceh Syariah aligns with the principles and provisions stipulated in the DSN-MUI fatwa, particularly regarding contract structure, ownership transfer mechanism, and risk allocation. However, the study also identifies several administrative and procedural aspects that require improvement, especially in documentation clarity and contract standardization, to ensure more comprehensive adherence to sharia principles. Strengthening these aspects is essential to enhance legal certainty and reinforce public trust in Islamic financial institutions.